2020
DOI: 10.1101/2020.02.14.949503
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unstructured mRNAs form multivalent RNA-RNA interactions to generate TIS granule networks

Abstract: The TIS granule network is a constitutively expressed membraneless organelle that concentrates mRNAs with AU-rich elements and interacts with the major site of protein synthesis, the rough endoplasmic reticulum. Most known biomolecular condensates are spherelike, but TIS granules have a mesh-like morphology. Through in vivo and in vitro reconstitution experiments we discovered that this shape is generated by extensive intermolecular RNA-RNA interactions. They are mostly accomplished by mRNAs with large unstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…However, in agreement with Iserman et al, we found that the structure of the RNA itself affects N condensation; base-paired or G-quadruplex-containing RNA produce irregularly shaped, gel-like condensates, similar to viral RNA (28). RNA may drive the formation of abnormal droplet shapes by forming networks of intermolecular base pairs, as previously reported (13,23,24,56).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, in agreement with Iserman et al, we found that the structure of the RNA itself affects N condensation; base-paired or G-quadruplex-containing RNA produce irregularly shaped, gel-like condensates, similar to viral RNA (28). RNA may drive the formation of abnormal droplet shapes by forming networks of intermolecular base pairs, as previously reported (13,23,24,56).…”
Section: Discussionsupporting
confidence: 92%
“…We concluded that unstructured and flexible polyanions form complex coacervates with the positively charged N protein (20) and trigger formation of liquid condensates. The structure of the RNA affects N phase separation, with secondary structures of RNA triggering formation of gel-like droplets (13,23,24). Phase separation of N with RNA was also dependent on protein-RNA stoichiometry.…”
Section: The N Protein Phase Separates With Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, a small amount of RNA initially promotes protein droplet formation and afterwards begins dissolving the droplets once the concentration of the RNA reaches a threshold [ 76 , 77 ]. RNAs change physical properties of condensates (i.e., viscosity), augment granule assembly in vitro and in vivo [ 13 , 44 , 67 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ], determine the three dimensional structure of granules in an RNA concentration-dependent manner [ 49 , 85 ], and can even instruct the morphology of granules by their ability to engage in intermolecular RNA-RNA interactions [ 86 ].…”
Section: Formation Of Rna Granules: the Role Of The Rnamentioning
confidence: 99%
“…Membrane-less compartments, such as Cajal bodies and nuclear speckles, are micron-sized assemblies of proteins or RNA-protein complexes formed by liquid-liquid phase separation (LLPS) (Shin and Brangwynne, 2017). Most are sphere-like but others such as the TIS granule network form mesh-like structures (Ma et al, 2020). In most cases LLPS involves RNA-binding proteins (RBPs) harbouring prion like domains (PLDs).…”
Section: Introductionmentioning
confidence: 99%